Life after Deportation. (May 2019) - Golash-Boza, Tanya; Ceciliano-Navarro, Yajaira
Deportees' reintegration is shaped by the contexts of reception in their countries of origin and the strength of their ties to the United States. For some, the deprivation and isolation of deportation is akin to a death sentence.